2022
DOI: 10.1002/advs.202200477
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Postoperative Recurrence of Early‐Stage Hepatocellular Carcinoma by a Wound‐Targeted Nanodrug

Abstract: New strategies to decrease risk of relapse after surgery are needed for improving 5‐year survival rate of hepatocellular carcinoma (HCC). To address this need, a wound‐targeted nanodrug is developed, that contains an immune checkpoint inhibitor (anti‐PD‐L1)and an angiogenesis inhibitor (sorafenib)). These nanoparticles consist of highly biocompatible mesoporous silica (MSNP) that is surface‐coated with platelet membrane (PM) to achieve surgical site targeting in a self‐amplified accumulation manner. Sorafenib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…[5] Effectively addressing the challenge of early recurrence and improving treatment outcomes necessitates the implementation of effective strategies, such as perioperative targeted therapy, immunotherapy, and transarterial chemoembolisation (TACE). [6][7][8][9] These approaches aim to target the residual tumor cells and impede their growth and dissemination postoperatively. However, accurately predicting which patients are at a high risk of early recurrence remains a complex task in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Effectively addressing the challenge of early recurrence and improving treatment outcomes necessitates the implementation of effective strategies, such as perioperative targeted therapy, immunotherapy, and transarterial chemoembolisation (TACE). [6][7][8][9] These approaches aim to target the residual tumor cells and impede their growth and dissemination postoperatively. However, accurately predicting which patients are at a high risk of early recurrence remains a complex task in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the FDA approved ICIs in combination with anti-angiogenic drugs for the treatment of patients with inoperable HCC or patients with HCC ineligible for transplantation [51]. Some studies have shown that antivascular strategies combined with immune checkpoint blockade can effectively improve the efficacy of immunotherapy [45,52]. VEGF can prevent T cells from infiltrating tumors by promoting endothelial nonreactivity; thus, it inhibits the anticancer effect of ICIs and leads to the apoptosis of CD8 + T cells.…”
Section: Immunotherapymentioning
confidence: 99%
“…Moreover, combination with anti-PD-1 therapy can reverse the inhibitory immune microenvironment of HCC. To solve the problem of HCC recurrence after surgery, Li et al [ 84 ] designed a bionic NDDS consisting of MSNPs loaded with anti-PD-L1 and sorafenib and coated with platelet membranes at the surface of the MSNPs. This NDDS can target wounds and generate potent anti-HCC immunity, providing a new therapeutic idea for preventing recurrence in postsurgery HCC patients.…”
Section: Immunotherapy-based Novel Nanoparticles In Hccmentioning
confidence: 99%